Perlindungan Hukum Bagi Konsumen Pada Kasus Perubahan Venue Konser DAY6 Oleh Promotor - Damayanti, Nurhaliza; Apriani, Rani (Peneliti.net, 2025)
This research aims to analyze the form of legal protection for consumers and assess the suitability of the concert promoter's actions, in changing the DAY6 concert venue suddenly against the provisions of consumer protection law in Indonesia. The research method used is the normative juridical method, namely by examining relevant laws and regulations, such as Undang-Undnag Nomor 8 Tahun1999 Tentang Perlindungan Konsumen (UUPK), KUHPerdata, as well as general principles in contract law and entertainment services.The results of the analysis show that consumers as users of entertainment services have the right to correct information, clarity of service, comfort, and the right to compensation in the event of adverse changes. In the case of the DAY6 concert venue change, the promoter's actions carried out suddenly without clear notification and compensation can be considered incompatible with the principles of transparency, good faith, and the responsibility of business actors as stipulated in Pasal 4, 7, and 19 of UUPK. In fact, these actions have the potential to qualify as default or illegal acts based on Pasal1243 and 1365 of the KUHPerdata.